Legal Analysis Regarding the Use of Artificial Intelligence (AI) in the Implementation of Medical Practice in Indonesia - Malik, Saputra; Suparno, Suparno (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. Health is a fundamental human need, alongside clothing, food, and shelter. A healthy life is essential for individuals to carry out daily activities, and without health, life becomes meaningless. The integration of Artificial Intelligence (AI) in healthcare offers solutions and enhances modern medical services. However, the use of AI in healthcare also raises concerns and potential risks. Purpose. This study aims to determine the legal protection available to patients in the use of AI and analyze the legal liability of doctors in employing AI technologies in medical practices. Method. This research adopts a normative juridical method, focusing on secondary data, including primary, secondary, and tertiary legal materials. The study examines legal frameworks and regulations to explore the aspects of patient protection and the liability of healthcare professionals using AI. Results. The study identifies two forms of legal protection for patients: preventive and repressive. Preventive protection includes ensuring the security of patient data before it is uploaded to AI systems, safeguarding privacy and data integrity. Repressive protection applies if a patient suffers harm due to AI usage; in such cases, patients can report the issue to authorities in accordance with relevant laws and regulations. The study also discusses the legal responsibility of both doctors and AI developers. Doctors using AI in treatment can be held liable if their use of AI results in harm to patients. Similarly, AI developers or creators can also be held legally accountable if their AI technology negatively impacts patient care. Legal liabilities could include criminal, civil, or administrative responsibility. Conclusion. AI plays a significant role in modern healthcare but also presents challenges regarding patient protection and professional liability. Clear legal protections, including preventive measures to secure patient data and repressive actions for harm, are essential. Both healthcare providers using AI and AI developers must be held accountable for any adverse outcomes, ensuring patient safety and trust in the healthcare system.